2022
DOI: 10.3390/info13070344
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on the Differences between Online Picture Reviews and Text Reviews

Abstract: In the context of e-commerce, online travel agencies often derive useful information from online reviews to improve transactions. Based on the dispute on the usefulness of different types of reviews and social exchange theory, this study investigates how the characteristics of pictures and text influence review reading and review posting behaviors and thus influencing the efficiency of online review systems. By analyzing crawled data of online hotels and conducting experiments, we first find that picture revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…However, the information value of eWOM decreases over time. In addition, previous research based on information overload theory has shown that the length of eWOM does not necessarily benefit future customers [34]. Therefore, we recognize Shukla et al's research on the impact of eWOM richness on user browsing time, which suggests that decision-making depends on online word-of-mouth richness in the market [35].…”
Section: Why Should We Pay Attention To the Frequency And Length Of U...mentioning
confidence: 78%
See 1 more Smart Citation
“…However, the information value of eWOM decreases over time. In addition, previous research based on information overload theory has shown that the length of eWOM does not necessarily benefit future customers [34]. Therefore, we recognize Shukla et al's research on the impact of eWOM richness on user browsing time, which suggests that decision-making depends on online word-of-mouth richness in the market [35].…”
Section: Why Should We Pay Attention To the Frequency And Length Of U...mentioning
confidence: 78%
“…Customers posting reviews is customer-driven sharing behavior. Many studies have researched customer motivations for sharing texts and pictures, but their conclusions have centered around customers [34,72]. Our research focuses on the richness of eWOM information from businesses, with the two independent variables of text and picture richness.…”
Section: Findings 41 Structural Modelmentioning
confidence: 99%